Patients attitude towards an alcohol content and halalness of cough medicines - Abdul Rahem (Journal of halal product and research (JPHR), 2019)
The halalness of medicines in Indonesia is an interesting case to study, given that the consumption of medicines and halal food is an obligation for the majority of Indonesia's Muslim population. Since the legalization of Law 33 of 2014 about Halal Product Assurance (UU JPH), there are still differences of opinion in several ministries in Republic Indonesia regarding the implementation of medicinal products, especially for medicines that are classified as life-saving. This research was conducted during August 2018 and aims to analyze the attitudes of cough sufferers towards the halalness of cough medicine and their attitude towards medicines containing alcohol. This study uses an observational design, the research variable is the attitude towards halal and alcohol content in drugs, and the drugs received. During one month, 25 respondents obtained in 5 apothecaries; 2 apothecaries in Bangkalan Regency and 3 apothecaries in Pamekasan Regency. The instrument used was a questionnaire. The results showed that 100 percent of patients wanted halal drugs and did not contain alcohol. From the data obtained, showed that 68 percent of patients received cough medicines containing alcohol between 2.50 – 10 percent.